Industrial training report: Universiti Kuala Lumpur Malaysian Spanish Institute (UniKL MSI) / Farah Izzati Mohamad Hashim - Mohamad Hashim, Farah Izzati (Universiti Teknologi MARA, Perlis, 2024)
The MOST precious and priceless moments that revolved for sixmonth of my internship placement at Universiti Kuala Lumpur Malaysian Spanish Institute (UniKL MSI) was one of the most invaluable experiences in my life. The journey of my industrial training at UniKL MSI started on 1st of March 2024 and ended on 9th of August 2024. I have been assigned to Academic Services Section (AcSS), supervised by Puan Norliza Amran. Day passing by days within the 24 weeks of my internship placement were truly a golden opportunity for me to get myself well prepared to enter the real working environment while being part of the requirement in the journey of completing my study as a Human Resource final year student. All of the precious experiences and knowledge that enriched both my professional skills and personal growth that I was able to gain because they provide an exposure to us as students on what a real-life working atmosphere feels like. Revolves in Academic Affairs department has taught me on how to manage documentations, handle databases and deal with people from various backgrounds. These are the elements that cannot be taught with papers and pens.